1987
DOI: 10.1159/000124718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dexamethasone on Central and Peripheral ACTH Systems in the Rat

Abstract: To investigate the simultaneous effects of dexamethasone on peripheral and central adrenocorticotropic hormone (ACTH) systems, rats were treated with dexamethasone or saline for 4 days. Pituitary, plasma, hypothalamus and cerebrospinal fluid (CSF) were then collected and analyzed for ACTH immunoreactivity. Additionally, hypothalamic tissue extracts were analyzed for corticotropin-releasing hormone (CRH) immunoreactivity. Dexamethasone significantly lowered peripheral levels of ACTH as measured in pituitary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…Several studies have examined the distribution of dex amethasone binding sites in brain, and have suggested that dexamethasone may act centrally to inhibit ACTH and cor ticosterone secretion [8,II]. In contrast, studies by De Kloet et al [5] and Carnes et al [4] indicate that dexametha sone can affect ACTH secretion by a more direct mecha nism at the level of the pituitary. What is clear from these and other studies is that even if dexamethasone acts directly on the pituitary, higher brain centers can influence the HPA axis, especially during stress [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the distribution of dex amethasone binding sites in brain, and have suggested that dexamethasone may act centrally to inhibit ACTH and cor ticosterone secretion [8,II]. In contrast, studies by De Kloet et al [5] and Carnes et al [4] indicate that dexametha sone can affect ACTH secretion by a more direct mecha nism at the level of the pituitary. What is clear from these and other studies is that even if dexamethasone acts directly on the pituitary, higher brain centers can influence the HPA axis, especially during stress [18].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone is a synthetic glucocorticoid which inhibits the secretion of ACTH and cortisol. acting at the level of the hypothalamus to block the release of CRH, and at the level of the pituitary gland to block the ACTH response to CRH (22). The study was carried out using two groups of eight rams during the regressing phase of the reproductive cycle (6 weeks after a change from short to long days).…”
Section: Lh Responses To Nmda 315mentioning
confidence: 99%
“…When a signal occurs approximately every 100 min, as in these larger ultradian secretory episodes, the Nyquist frequency demands that the sampling interval be at least half the signal frequency, i.e., 50 min, in order to detect the signal [ 15]. Most previous investi gations of rhythmic secretion of ACTH in the rat have sacrificed groups of animals at different times of day, usually at 4-hour intervals or greater [ 1,2,8,11,13], This sampling interval is too long to detect ultradian rhythms. In addition, when groups of different animals are used at each time point, the individual va riation among animals in plasma ACTH levels tends to flatten out the data and obscure any rhythm.…”
Section: Larger Ultradian Rhythmmentioning
confidence: 99%